Early detection of brain metastases in a supervised exercise program for patients with advanced breast cancer: a case report - Pelaez, Mireia; Stuiver, Martijn M.; Broekman, Marike; Schmitz, Kathryn H.; Zopf, Eva M.; Clauss, Dorothea; Wengström, Yvonne; Rosenberger, Friederike; Steindorf, Karen; Urruticoechea, Ander; May, Anne M. (Medicine and science in sports and exercise, 2023)
Introduction - Around 25% of metastatic breast cancer (mBC) patients develop brain metastases, which vastly affects their overall survival and quality of life. According to the current clinical guidelines, regular magnetic resonance imaging screening is not recommended unless patients have recognized central nervous system-related symptoms. - Patient Presentation - The patient participated in the EFFECT study, a randomized controlled trial aimed to assess the effects of a 9-month structured, individualized and supervised exercise intervention on quality of life, fatigue and other cancer and treatment-related side effects in patients with mBC. She attended the training sessions regularly and was supervised by the same trainer throughout the exercise program. In month 7 of participation, her exercise trainer detected subtle symptoms (e.g., changes in movement pattern, eye movement or balance), which had not been noticed or reported by the patient herself or her family, and which were unlikely to have been detected by the oncologist or other health care providers at that point since symptoms were exercise related. When suspicion of brain metastases was brought to the attention of the oncologist by the exercise trainer, the response was immediate, and led to early detection and treatment of brain metastases. - Conclusion and clinical implications - The brain metastases of this patient were detected earlier due to the recognition of subtle symptoms detected by her exercise trainer and the trust and rapid action by the clinician. The implementation of physical exercise programs for cancer patients requires well-trained professionals who know how to recognize possible alterations in patients and also, good communication between trainers and the medical team to enable the necessary actions to be taken.